A STABILITY RESULT FOR AN INVERSE PROBLEM WITH INTEGRODIFFERENTIAL OPERATOR ON A FINITE INTERVAL - Mosazadeh, Seyfollah; Koyunbakan, Hikmet (Rocky Mt Math Consortium, 2020)
A boundary value problem consisting of an integrodifferential equation, together with boundary conditions dependent on the spectral parameter, is investigated. The asymptotic behavior of the eigenvalues is studied, and we prove the uniqueness and the stability theorems for the solution of the inverse problem.
Keywords: inverse problem; integrodifferential equation; Volterra integral operator; uniqueness theorem; stability theorem